2010
DOI: 10.1007/s00062-010-0035-4
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Sandhoff Disease

Abstract: Sandhoff disease is a rare and severe lysosomal storage disorder representing 7% of GM2 gangliosidoses. Bilateral thalamic involvement has been suggested as a diagnostic marker of Sandhoff disease. A case of an 18-month-old infant admitted for psychomotor regression and drug resistant myoclonic epilepsy is presented. Cerebral CT scan showed bilateral and symmetrical thalamic hyperdensity. MRI revealed that the thalamus was hyperintense on T1-weighted images and hypointense on T2-weighted images with a hypersig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 8 publications
1
21
0
1
Order By: Relevance
“…A diagnostic neuroimaging marker of Sandhoff disease is bilateral thalamic involvement. 3 A recent advanced diagnostic modality for this disease is proton Magnetic Resonance Spectrography (MRS) of the cerebral metabolites. Wilken et al in their study identified increased levels of inositol (glial marker) and reduced amount of total N-acetylaspartate which is a neuroaxonal marker in a proved case of Sandoff disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A diagnostic neuroimaging marker of Sandhoff disease is bilateral thalamic involvement. 3 A recent advanced diagnostic modality for this disease is proton Magnetic Resonance Spectrography (MRS) of the cerebral metabolites. Wilken et al in their study identified increased levels of inositol (glial marker) and reduced amount of total N-acetylaspartate which is a neuroaxonal marker in a proved case of Sandoff disease.…”
Section: Discussionmentioning
confidence: 99%
“…2 Sandhoff disease represents 7% of GM2 gangliosidoses. 3 Here we report one such rare case of Sandhoff disease.…”
Section: Introductionmentioning
confidence: 87%
“…27 O caso da Doença de Sandhoff encontrado neste trabalho apresenta quadro clínico semelhante ao apresentado em um relato de caso sobre esta doença, no qual descreveu um paciente do gênero masculino (um ano e seis meses), que também apresentava regressão psicomotora e a mancha vermelho-cereja na retina, inicio dos sintomas aos seis meses de vida e pais consanguíneos (primos de primeiro grau). 28 Foi possível concluir neste trabalho, que o EIM repercute negativamente no estado nutricional dos pacientes, uma vez que as duas crianças que tiveram diagnóstico apresentaram algum distúrbio nutricional.…”
Section: Variávelunclassified
“…In Krabbe's disease T2 hypointensity is more extensive involving the basal ganglia, central white matter and cerebellum in addition to thalamus. [1] Presence of bithalamic T2 hypointensity is a characteristic feature of lysosomal storage disease and helps in performing limited specific investigations for diagnosis of inherited neurometabolic disorders. …”
mentioning
confidence: 99%
“…Clinical features include muscular hypotonia or hypertonia, tonico-clonic or myoclonic seizures, visual deficit, and psychomotor retardation. [1] Computed tomography (CT) brain features include bilateral symmetric thalamic hyperdensity with non-specific bilateral white matter hypodensity. MRI is the imaging modality of choice and shows characteristic bilateral thalamic T2 hypointensity and putaminal T2 hyperintensity.…”
mentioning
confidence: 99%